Design of the controller cooling system of an electric vehicle - Rahman M.M.; Hua T.J.; Rahman H.Y. (Trans Tech Publications Ltd, 2023)
As an effort in reducing the dependency on fossil fuel, efforts have been gathered to develop electric vehicle (EV) for the past decades. Technology of electric vehicles (EV) has been initialized in developed countries. However, the latter have different geographical and environmental conditions. Therefore, the system of EV cannot be utilized directly in this country. The controller of an EV functions by utilizing a potentiometer; supplying a certain amount of voltage from the batteries to the motor by driver’s force applied to the acceleration pedal. This action generates a huge amount of heat due to the internal resistance of the controller (e.g. potentiometer). In order for an EV to operate at optimum condition, temperature of the controller has to be maintained at a certain limit. Hence an effective cooling system is required to be designed to fulfill the above condition. The objective of this paper is to present the design of the cooling system for the controller of an electric vehicle (EV). Two types of cooling system namely liquid cooled plate heat exchanger and forced air cooled finned structure are designed and evaluated to assess the behavior of heat transfer as well as effects of heat transfer fluids and cooling system material towards the heat removal rate. Simulation using Computational Fluid Dynamics (CFD) for both cooling systems has been carried out to have better understanding. CFD results are compared with some of the analytical results. The findings revealed that both systems are suitable to be implemented as EV controller cooling system in Malaysian Environment. © (2014) Trans Tech Publications, Switzerland.